Vpliv dejavnikov na vpis učencev v Srednjo zdravstveno šolo v Mariboru - Unterlechner, Silva (Obzornik zdravstvene nege, 1999)
The present research study is based on a questionaire consisting of 20 quenstions. One hundred and thirty-four students of the High School of NursingJuga Polak in Maribor were investigated. The results are exhaustively presented in the discussion of the questionnaire. Relative importance of the motivation towards the collective, age correlation, status distribution, education of parents, school grades and gender is shown. Dimensions of motivesfor independence, cooperation and belonging are indicated.
Keywords: Adolescence; ankete; Decision making; education; Education, nursing; Health occupations; izobraževanje; Schools, nursing; srednje šole; učenci; zdravstvene šole